2008
DOI: 10.1083/jcb.200706189
|View full text |Cite
|
Sign up to set email alerts
|

Cdk11 is a RanGTP-dependent microtubule stabilization factor that regulates spindle assembly rate

Abstract: Production of Ran–guanosine triphosphate (GTP) around chromosomes induces local nucleation and plus end stabilization of microtubules (MTs). The nuclear protein TPX2 is required for RanGTP-dependent MT nucleation. To find the MT stabilizer, we affinity purify nuclear localization signal (NLS)–containing proteins from Xenopus laevis egg extracts. This NLS protein fraction contains the MT stabilization activity. After further purification, we used mass spectrometry to identify proteins in active fractions, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 29 publications
1
89
0
6
Order By: Relevance
“…CSF extracts were supplemented with Cy3-labelled tubulin and incubated with sperm nuclei or chromatin beads for spindle assembly 30 . Microtubule density around sperm or beads was quantified using Matlab (The MathWorks) 31 . For rescue experiments, mRNA encoding Xenopus MEL-28 (GenBank accession KJ026765) was prepared using the mMESSAGE mMachine kit (Life Technologies) and added to extracts at a concentration of 300 ng ml À 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CSF extracts were supplemented with Cy3-labelled tubulin and incubated with sperm nuclei or chromatin beads for spindle assembly 30 . Microtubule density around sperm or beads was quantified using Matlab (The MathWorks) 31 . For rescue experiments, mRNA encoding Xenopus MEL-28 (GenBank accession KJ026765) was prepared using the mMESSAGE mMachine kit (Life Technologies) and added to extracts at a concentration of 300 ng ml À 1 .…”
Section: Methodsmentioning
confidence: 99%
“…His, GFP-tagged aa 1,441-2,201 was constructed in pET28a (Novagen), expressed in E. coli and purified with Ni-NTA and Superose 6 (GE Healthcare Life Sciences). His-importin-a, His-importin-b and His-RanQ69L-GTP were expressed in E. coli and purified with TALON beads (Clontech) 31 .…”
Section: Methodsmentioning
confidence: 99%
“…[14][15][16][17][18][19] It is important therefore not to simply focus on how CDK11 regulates components of the autophagy machinery to bring about the effects we report knocked down by siRNA (Fig. 3A).…”
Section: Pitslre Is a Modulator Of Autophagymentioning
confidence: 99%
“…13 Subsequent studies on PITSLRE/CDK11 have revealed diverse roles for the kinase in controlling RNA splicing, apoptosis, sister chromatid adhesion and cytokinesis. [14][15][16][17][18][19] We add to these roles by showing that CDK11 is a fundamental regulator of autophagy. We show that while CDK11 appears to act as a turnover.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of nuclear envelope breakdown (NEBD), another Ran-GTP gradient is generated around the chromosomes, to which the RCC1 GTP-exchange factor binds (Clarke 2008). This Ran-GTP gradient is important for the interaction between microtubules and chromosomes because the high Ran-GTP levels around chromosomes promote the dissociation between the importin b chaperone and its binding partners, several of which help to stabilize or nucleate microtubules (Carazo-Salas et al 1999;Kalab et al 1999;Gruss et al 2001;Wilde et al 2001;Yokoyama et al 2008).…”
mentioning
confidence: 99%